Library usage patterns of the University of Perpetual Help System DALTA as affected by factors on students' personal attributes, background characteristics, faculty, user needs, library resources, services and facilities - Orillaza, Jose Miguel G. (2011)
This study deals with library usage patterns of the University of Perpetual Help System DALTA as affected by factors on students' personal attributes, background characteristics, faculty, user needs, library resources, services and facilities of the UPHSD Library and Media Center. Specifically, the study aimed to determine: (1) how students' personal attributes such as age, gender, year level, academic performance, academic load, income level and distance of residence from campus affect library usage, (2) how background characteristics in terms of students' previous library experience, familiarity in using libraries, library instruction attended, library orientation attended and computer literacy affect library usage, (3) how faculty members affect library usage through their encouragement, course/subject requirements and student-faculty interactions, (4) how users' perceived needs affect library usage and (5) how students assessment of the UPHSD Library and Media Centers' resources, services and facilities affect library usage.